Implementasi Pembiasaan Shalat Dhuha dan Shalat Dhuhur secara Berjamaa’ah dalam Membentuk Karakter Disiplin di MI Tarbiyatul Islam Kraksaan - Alfina Muniffatuz Zahra’; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the influence of the habit of Dhuha and Dhuhur prayers in congregation on the formation of students' disciplined character at MI Tarbiyatul Islam Kraksaan. Regular congregational prayers at school are an effective method for teaching disciplinary values ​​and strengthening students' spirituality. Through this activity, students are taught to respect time, obey rules, and develop social responsibility. This research uses a descriptive qualitative approach with a case study method. Data was obtained through observation, interviews and documentation to describe the process and impact of getting used to congregational prayers on student discipline. The results of the research show that the habit of praying in congregation at MI Tarbiyatul Islam has a positive impact in shaping students' disciplined character. It is hoped that the implementation of this habit will become a model for other educational institutions in integrating character education through a worship approach.